"Les Inconnus de la resistance": letters to L’Humanité, 1984 - Gildea, R (University of Western Australia, 2017)
In 1984 the Communist daily 'L'Humanite' invited its readers to send in testimonies of resistance activity in Vichy and German-occupied France. The project may be seen as an attempt by the Communist Party to recover some legitimacy at a moment when its wartime record was under attack and electoral support in decline. An analysis of the 400 letters received nevertheless also allows us to explore what ordinary people thought resistance was: was it the heroic, organised actions of the few or the sporadic, spontaneous and symbolic gestures of the many?